2021
DOI: 10.17533/udea.iee.v39n3e11
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes in vision during aging: perceptions of older adults and healthcare providers

Abstract: Objective. To identify the physiological changes in older adults’ vision during the aging process. Methods. An exploratory, descriptive study with a qualitative approach was conducted with 20 older adults and six healthcare providers who worked with older adults in João Pessoa, Paraíba (Brazil). The Focus Group Technique was used for data collection, with the collected information subsequently being submitted to Inductive Thematic Analysis using textual analysis software. Results. The physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(21 reference statements)
0
4
1
Order By: Relevance
“…In contrast, a study done in India found that the prevalence of all ocular morbidities was signi cantly associated with increasing age [23]. Physiologically, eye care conditions increase with age [24]. Again, the results of our study can be due to the small sample size and narrow age range employed.…”
Section: Discussioncontrasting
confidence: 81%
“…In contrast, a study done in India found that the prevalence of all ocular morbidities was signi cantly associated with increasing age [23]. Physiologically, eye care conditions increase with age [24]. Again, the results of our study can be due to the small sample size and narrow age range employed.…”
Section: Discussioncontrasting
confidence: 81%
“…In contrast, a study done in India found that the prevalence of all ocular morbidities was significantly associated with increasing age 22 . Physiologically, eye care conditions increase with age 23 . Again, the results of our study can be due to the small sample size and narrow age range employed.…”
Section: Discussionmentioning
confidence: 60%
“…22 Physiologically, eye care conditions increase with age. 23 Again, the results of our study can be due to the small sample size and narrow age range employed. | of 5 In this present study, more females than males visited the clinic with ocular morbidities similar to the pattern observed at a government health facility in the district.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Population ageing is a common phenomenon occurring all around the world, which causes an increasing demand for elderly care (Fulmer et al, 2021 ). Ageing results in physiological changes, the more distinct of which include decreased lung function, increased blood pressure, deteriorating vision or hearing, changes in activity and behaviour, and chronic diseases induced by degenerating organs (Cordeiro et al, 2021 ). The prevalence of disability also increases rapidly with age.…”
Section: Introductionmentioning
confidence: 99%